(3CeGdj GHf GdTLQjs - (3GHf GdTLQj , gHI Gddg Hf Ydj Hf eMeO GdMSfj, CHh GdSYGOGJ,J (B542 (3g` s
(3ChdgG (B:s
(3GdeLdS GdSGOS hGdNeShf jJVef eSGFd GdJQNje heG jJUd HgG heG de JSJYedg GdYQH EdG aj GdfOGA cfJ MOOJ GdePgH GdeNJGQ ef ePgHj GdJQNje s
(3BNQgG (B:s
(3ef GdeLdS GdKGdK hGdKeGfjf abGd YGHfj CQGPd GdfGS aefge ef QeGfj HYjH gh ajg hgh GdCHfI hGfbdH bhdg Ydjg aCUGH CSJg HGdYjH GdPj QeGfj Hg Cj GdPjf Qehfj ef gPjf GdUfajf hHgPjf GdhUajf s
(3GdfSNI HgG MhGTs
(3HgG JUMjMGJs
(3YdjgG HYV ebGHdGJs
(3ef fSNI QGHYI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdCOHs